Comic-Based Microlearning Worksheets to Improve Elementary Students’ Numeracy Skills and Motivation - Rita Ratna Sari; Intan Dwi Hastuti; Zulkarnain Zulkarnain; Moses Adeleke Adeoye; Zohaib Hassan Sain (Profesi Pendidikan Dasar, 2026)
Numeracy skills and learning motivation are important competencies that need to be developed at elementary school level. However, conventional learning methods have not fully supported the development of these competencies. This study aims to analyse the effect of integrating comic-based microlearning with student worksheets on the numeracy skills and learning motivation of elementary school students. A quantitative approach with a quasi-experimental design was used, involving a control group of 30 fourth-grade students divided into an experimental group and a control group. Data were collected through numeracy ability tests and learning motivation questionnaires. Analysis of the results showed a significant difference in numeracy ability and learning motivation between the two groups. These findings suggest that integrating Student Worksheets with comic-based microlearning effectively improves elementary school students' numeracy skills and learning motivation in a meaningful, contextual manner. Therefore, this learning model has the potential to serve as an innovative, relevant alternative learning medium for elementary school students, providing empirical contributions to the development of visual and digital learning media for numeracy learning.